Growing Up With Terrorism: The Age at Which a Terrorist Attack Was Suffered and Emotional Disorders in Adulthood - Prieto, Sara; Sanz, Jesús; García-Vera, María Paz; Fausor, Rocío; Morán, Noelia; Cobos, Beatriz; Gesteira, Clara; Navarro, Roberto; Altungy, Pedro (Frontiers in Psychology, 2021)
Abundant scientific literature shows that exposure to traumatic situations during childhood or adolescence has long-term psychopathological consequences, for example, in the form of a higher prevalence of emotional disorders in adulthood. However, an evolutionary perspective suggests that there may be differential vulnerabilities depending on the age at which the trauma was suffered. As there are no studies on the psychopathological impact in adulthood of attacks suffered during childhood or adolescence, the objective of this study was to analyze the influence of the age at which a terrorist attack was suffered in the presence of emotional disorders many years after the attack. A sample of 566 direct and indirect victims of terrorist attacks in Spain was recruited, of whom 50 people were between the age of 3 and 9 when they suffered the attack, 46 were between 10 and 17 years old, and 470 were adults. All of them underwent a structured diagnostic interview (SCID-I-VC) an average of 21 years after the attacks. No significant differences were found between the three age groups at which the attack occurred in terms of the current prevalence of post-traumatic stress disorder, major depressive disorder, or anxiety disorders. The results of several multiple binary logistic regression analyses also indicated that, after controlling for the effect of sex, current age, the type of victims, and the time since the attack, the age at which the attack was suffered was not related to the current prevalence of these emotional disorders. The results are discussed concerning the differences between various types of trauma and in the context of the theories that propose that traumatic experiences are processed differently at different ages and can lead to differences in the likelihood of developing different emotional disorders.